Infectivity assessment of porcine endogenous retrovirus using high-throughput sequencing technologies. (June 2021) - Kono, Ken; Kataoka, Kiyoko; Yuan, Yuzhe; Yusa, Keisuke; Uchida, Kazuhisa; Sato, Yoji
Abstract: Xenogenic cell-based therapeutic products are expected to alleviate the chronic shortage of human donor organs. For example, porcine islet cell products are currently under development for the treatment of human diabetes. As porcine cells possess endogenous retrovirus (PERV), which can replicate in human cells in vitro, the potential transmission of PERV has raised concerns in the case of products that use living pig cells as raw materials. Although several PERV sequences exist in the porcine genome, not all have the ability to infect human cells. Therefore, polymerase chain reaction analysis, which amplifies a portion of the target gene, may not accurately assess the infection risk. Here, we determined porcine genome sequences and evaluated the infectivity of PERVs using high-throughput sequencing technologies. RNA sequencing was performed on both PERV-infected human cells and porcine cells, and reads mapped to PERV sequences were examined. The normalized number of the reads mapped to PERV regions was able to predict the infectivity of PERVs, indicating that it would be useful for evaluation of the PERV infection risk prior to transplantation of porcine products.